Advancements in pseudouridine modifying enzyme and cancer - Liu, Kaijie; Zhang, Shujun; Liu, Yafeng; Hu, Xinjun; Gu, Xinyu (Frontiers in Cell and Developmental Biology, 2024)
Pseudouridine (Ψ) is a post-transcriptional modifier of RNA, often referred to as the ‘fifth nucleotide’ owing to its regulatory role in various biological functions as well as because of its significant involvement in the pathogenesis of human cancer. In recent years, research has revealed various Ψ modifications in different RNA types, including messenger RNA, transfer RNA, ribosomal RNA, small nuclear RNA, and long noncoding RNA. Pseudouridylation can significantly alter RNA structure and thermodynamic stability, as the Ψ-adenine (A) base pair is more stable than the typical uridine (U)-A base pair is due to its structural similarity to adenine. Studies have linked Ψ expression to the development and progression of several digestive system cancers, such as liver cancer and colorectal cancer, and nondigestive system cancers, such as breast cancer, non-small cell lung cancer, prostate cancer, glioblastoma, ovarian cancer, oral squamous cell carcinoma, and pituitary cancer. The present review briefly outlines the chemical structure, synthesis, and regulatory mechanisms of Ψ. This review summarizes the effects of pseudouridylation on various substrates of RNA and briefly discusses methods for detecting Ψ. Last, it focuses on how RNA pseudouridylation influences different cancers, emphasizing the search for novel approaches to cancer diagnosis, treatment, and prognosis through Ψ modification.